BERBAGAI FAKTOR YANG MEMPENGARUHI WISATAWAN MENGUNJUNGI OBJEK WISATA DI KABUPATEN LANGKAT - Muhammad Halfi Indra Syahputra (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Forest preservation really needs to be maintained where forests have many benefits for human life, one of which is the use of environmental services, tourism, such as the location that is the object of this research, where Langkat Regency has a tourist attraction that is motivated by the beauty of nature and its forests. This type of research uses associative quantitative descriptive method. Associative quantitative research method is research that aims to determine the effect or relationship between two or more variables. Where based on the research results the relationship between the variables in this study it can be concluded that attractions, facilities, and accessibility are very influential and simultaneously interrelated to the decision to visit.